1980
DOI: 10.1016/0038-1098(80)90270-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal spin polarization and symmetries in low-energy-electron diffraction: Experiment and theory for Pt(111)

Abstract: In low-energy electron diffraction from Pt(1 11), the longitudinal component of the spin polarization vector and its transverse component normal to the scattering plane were measured by a Mott detector and found to agree very well with corresponding theoretical results. Rotation diagrams of the longitudinal and transverse components exhibit only a three-fold symmetry in contrast to the six-fold symmetry, which time reversal invariance dictates for intensities.IN ELASTIC electron-atom scattering with an high-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Symmetry considerations predict an even behavior A(P n ,ϕ) = A(P n ,−ϕ) [35]. This condition agrees with our experimental results within error limits.…”
Section: Fig 6 Intensity Asymmetry and Relative Fom Maps Of P N (Asupporting
confidence: 82%
“…Symmetry considerations predict an even behavior A(P n ,ϕ) = A(P n ,−ϕ) [35]. This condition agrees with our experimental results within error limits.…”
Section: Fig 6 Intensity Asymmetry and Relative Fom Maps Of P N (Asupporting
confidence: 82%
“…Here a detailed description of the modified set-up is given, which was briefly sketched in ref. [2]. The apparatus (see fig.…”
Section: Methodsmentioning
confidence: 99%
“…8). For the polarization components P~ and Pk the symmetry stays threefold, however, as has already been shown [8,15,26]. As regards only the P~(~0) diagrams of Fig.…”
Section: Resultsmentioning
confidence: 60%
“…The two polarization components parallel to the scattering plane therefore generally do not vanish owing to multiple scattering. For Pt(lll), for example, it has been shown that the longitudinal component Pk, which is parallel to the momentum of the outgoing beam, may contain information [8]:…”
Section: Introductionmentioning
confidence: 99%